The historical, typological and cultural significance of the yurt – the traditional dwelling of the Turkic peoples of Central Asia - Ateş Омер Фарух; Ibrayeva Гулжан (Turkic Studies Journal, 2025)
The dwelling is one of the most important objects of historical and ethnographic research on the culture of the Turkic peoples. The examination of traditional dwellings of any people depends on a several factors, including knowledge of their social structure, economic activities, and stages of socioeconomic and cultural development. The relevance of studying the dwellings of the Turkic peoples lies in the need to trace their historical and chronological evolution and to identify the ideological and ethnocultural constants that shaped the development and functioning of various types of dwellings among them over many centuries. To achieve these objectives and analyze dwelling forms in nomadic culture, the authors of this article draw on ancient, medieval Arab-Persian, and Chinese sources. The study reveals that both nomadic and sedentary dwellings of diverse designs coexisted within Turkic culture. These include huts covered with tree bark, South Siberian polygonal log structures, Central Asian yurts covered with felt, and various transitional forms of dwellings. The primary economic activity of the Turkic peoples was livestock breeding, associated with seasonal migrations, for which the yurt – a portable dwelling – proved to be the most practical and convenient. Based on the historical sources, this article examines different scholarly perspectives on the origins and development of the yurt, identifying its earliest forms among the Saka/Scythians and the Huns, the ancient ancestors of the Turks. The design, regional variations, and functional significance of the yurt within the cultures of the Turkic and Mongolian peoples of Eurasia are analyzed in a comparative cultural context. The authors difine the yurt not only as a practical, easily erected dwelling adapted to the nomadic way of life but also as an ethnocultural phenomenon closely linked to spiritual beliefs, social organization, and symbolic space. The study provides a comparative systematization of yurt forms common in Central Asia and among the Siberian Turks, whose lifestyle was predominantly semi-nomadic. It is shown that, despite the shared structural components of the yurt – ‘kerege’, ‘uyk’, and ‘shanyrak’ – regional variants differ in the curvature of the ‘uyk’, the design of the ‘shanyrak’, and the materials used for covering, reflecting the ethnocultural and geographical diversity of the Turkic and Mongolian peoples. Particular attention is devoted to the adaptation and refinement of the yurt by Siberian peoples such as the Tuvans, Khakass, and Altaians, in accordance with their natural environments.